Good Corporate Governance’s Role in Green Strategy, Innovation, and Carbon Disclosure - Wilasittha, Acynthia Ayu; Aini, Evinda Dwi Nur (Universitas Prasetiya Mulya, 2025)
This study examines the relationship between carbon emission disclosure and green strategy and green innovation, with Good Corporate Governance (GCG) as a moderating variable. Employing a quantitative approach, the research utilizes secondary data sourced from annual reports and sustainability reports. The population comprises consumer non-cyclical companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. Using purposive sampling with specific criteria, a total of 44 companies were selected as samples over the three-year period. The findings reveal that both green strategy and green innovation significantly influence carbon emission disclosure, indicating that companies effectively implementing these practices tend to optimize their emission disclosures to enhance their reputation among stakeholders. Furthermore, the association between green strategy and carbon emission disclosure is not moderated by GCG, but it is strongly moderated by the relationship between green innovation and disclosure. This suggests that some consumer non-cyclical companies have yet to fully implement GCG, limiting the support for green strategies to maximize emission disclosure. Optimizing GCG implementation is therefore essential to reinforce both green strategy and green innovation, enabling companies to become more environmentally responsible and reduce operational carbon emissions, ultimately advancing corporate sustainability.